The formulation of disjunctivism about Φ-ing for a reason - Cunningham, JJ (Oxford University Press, 2018)
We can contrast rationalising explanations of the form S φs because p with those of the form S φs because S believes that p. According the Common Kind View, the two sorts of explanation are the same. The Disjunctive View denies this. This paper sets out to elucidate the sense in which the Common Kind Theorist asserts, but the Disjunctivist denies, that the two explanations are the same. I suggest that, in the light of the distinction between kinds of explanation and particular explanations, the relevant sameness thesis is ambiguous, thus giving us two distinct versions of the Common Kind View. I then argue that the only direct arguments for Disjunctivism available in the literature fail because they only succeed in undermining one version of the Common Kind View. I finish, however, by providing a fresh argument for the Disjunctive View which aims to undermine both versions of its competitor.